2012
DOI: 10.1016/j.contraception.2012.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of the etonogestrel implant in women undergoing immediate postabortion placement

Abstract: Objective-To estimate whether women who receive an immediate postabortion etonogestrel subdermal implant have higher discontinuation rates than women who undergo an interval insertion (insertion not associated with a recent pregnancy).Methods-This was a secondary analysis of the Contraceptive CHOICE Project. We compared 12-month continuation rates for the subdermal implant between women undergoing immediate postabortion placement and women who underwent an interval placement. Continuation rates were compared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…On the other hand, the result was higher than the studies conducted in Nigeria (26.1%), Tigray region (16%), and Malaysia (22.86%) [9,14,15]. This might be due to the educational status of the study participants [14,15], low male partners' involvement, and low practice of discussion with partners before the Implanon insertion [18]. Implanon as compared to women who developed side effects which is similar with the study done at Durame Town, Southern Ethiopia, Debre Markose, Northwest Ethiopia and Egypt [9,16,19,20].…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…On the other hand, the result was higher than the studies conducted in Nigeria (26.1%), Tigray region (16%), and Malaysia (22.86%) [9,14,15]. This might be due to the educational status of the study participants [14,15], low male partners' involvement, and low practice of discussion with partners before the Implanon insertion [18]. Implanon as compared to women who developed side effects which is similar with the study done at Durame Town, Southern Ethiopia, Debre Markose, Northwest Ethiopia and Egypt [9,16,19,20].…”
Section: Discussioncontrasting
confidence: 58%
“…his might be due to inadequate follow-up counseling and unexpected side effects of the method. On the other hand, the result was higher than the studies conducted in Nigeria (26.1%), Tigray region (16%), and Malaysia (22.86%) [9,14,15]. This might be due to the educational status of the study participants [14,15], low male partners' involvement, and low practice of discussion with partners before the Implanon insertion [18].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Published evidence showed that the continuation rate of Implanon ® after 2 years was 47% in a Scottish population 25. A possible explanation for this is that these LARC methods are known to have side effects such as irregular bleeding, which have been found to be one of the main reasons for their discontinuation 26 27. Furthermore, missed appointments and irregular bleeding are the main reasons for poor continuation rates of Depo-Provera 28.…”
Section: Discussionmentioning
confidence: 99%
“…For women who receive immediate postabortion IUDs and implants, method satisfaction and continuation rates are high (GRADE 1B) [67,[70][71][72]. In two prospective studies, the subdermal implant continuation rates at 12 months were similar for women who had the implant placed immediately after abortion and women who had an interval placement [70,72].…”
Section: What Are the Advantages Of Providing Immediate Postabortion mentioning
confidence: 99%